Peran Dinas Sosial Dalam Mendukung Program Pelayanan Kesehatan Bagi Lansia (Studi Kasus Di Dinas Sosial Kota Surabaya) - Razak, Rukmini; Oktarina, Oktarina; Paramita, Astridya (Jurnal Penelitian Kesejahteraan Sosial, 2021)
In five decades (1971-2017), the percentage of the elderly population in Indonesia has doubled, namely 8.97 percent (23.4 million people). The number of elderly in East Java ranks third at 12.16% in Indonesia, while in the city of Surabaya it reached 227,527 people (7.90 percent). For this reason, a special program for the elderly is needed for their survival to stay healthy and productive. This study aims to analyze the role of the Social Service in supporting health care programs for the elderly in the city of Surabaya. This research is a case study with a qualitative approach in the Surabaya Social Service. Data collection with in-depth interviews and focus group discussions was conducted with the Head of Social Rehabilitation for the Surabaya City Social Service and the Head of the Section for Rehabilitation of Children and the Elderly Social Tuna and staff, the East Java Pronvisi Health Service and the City of Surabaya. The results of the study inform the set of policies and regulations related to the welfare and health of the elderly have been available and implemented through a social service program by the Surabaya City Social Service. The program is in the form of food, gymnastics, elderly family development, training or entrepreneurship technical guidance and UPTD Griya Wredha. The implementation of the program did not get significant obstacles because the Surabaya Mayor's commitment was very high, so that Surabaya City was awarded the title as a Friendly Friendly City. The Social Service plays an important role in supporting health services, both in collaborative activities with the Health Service, Puskesmas, Elderly Posyandu and cross sector partnership activities through the Elderly-Friendly City. It requires commitment, partisanship and high concern and support for adequate allocation of funds from local governments for the success of the program Elderly welfare services, as has been demonstrated by the City of Surabaya.